SARS-CoV-2 Screening Test for Japanese Returnees From Wuhan, China, January 2020. (20th June 2020) - Kutsuna, Satoshi; Suzuki, Tadaki; Hayakawa, Kayoko; Tsuzuki, Shinya; Asai, Yusuke; Suzuki, Tetsuya; Ide, Satoshi; Nakamura, Keiji; Moriyama, Yuki; Kinoshita, Noriko; Hosokawa, Naoto; Osawa, Ryosuke; et al.
Abstract: Background: Severe acute respiratory syndrome–related coronavirus 2 (SARS-CoV-2) was found to be the causative microorganism of coronavirus disease 2019 (COVID-19), which started to spread in Wuhan, China. This study was to evaluate the effectiveness of questionnaire, symptoms-based screening, and polymerase chain reaction (PCR) screening of returnees from COVID-19-endemic areas on a chartered flight, to examine the proportion of infected persons and the proportion of asymptomatic persons among infected persons who returned from Wuhan. Methods: A retrospective cohort study was done in 7 tertiary medical institutions in Japan. A total of 566 Japanese who returned from Wuhan participated in the study. Results: Overall, 11 of the 566 passengers had a positive SARS-CoV-2 PCR result for pharyngeal swabs and 6 were asymptomatic. Only fever differed between SARS-CoV-2-positive and -negative individuals ( P < .043). Six of the 11 PCR-positive individuals were asymptomatic; 4 remained positive on day 10, and 1 asymptomatic person tested positive up to day 27. Two of the 11 were negative on the first PCR test and positive on the second. Conclusions: Our results will be important insights on screening returnees from locked-down cities, as well as providing important data on the proportion of asymptomatic individuals infected with SARS-CoV-2. A 13-day observation period and a second round of PCR may be effective to screen patients, including asymptomatic infections.